The level of antiretroviral drug resistance at Nkensani Hospital Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome Treatment Site - Machethe, K. F. (University of Limpopo, 2014)
Consult the document
Thesis (M.Sc. (Pharmacology)) --University of Limpopo, 2014
Keywords: Antiretroviral; Human Immunodeficiency virus; Acquired Immune Deficiency sydrome; Drug resistance; 615.1969792; AIDS Disease - Prevention; AIDS vaccine